A Meta-Analytic Review of Preschool Social and Emotional Learning Interventions - Murano, Dana; Sawyer, Jeremy E.; Lipnevich, Anastasiya A. (Review of educational research, 2020)
This meta-analysis summarized the effects of universal and targeted social and emotional learning (SEL) interventions in 48 studies on the development of social and emotional skills and the reduction of problem behaviors in 15,498 preschool students. For universal SEL interventions delivered to all students, a random-effects model with 33 primary studies showed small to medium effects for the overall development of social and emotional skills (Hedges’s g = .34) and for the reduction of problem behaviors (g = .32), with an overall grand mean of g = .35. For targeted interventions, delivered to at-risk students identified as being in need of additional supports, a random-effects model with 15 primary studies showed medium effects for the overall development of social and emotional skills (Hedges’s g = .44) and for the reduction of problem behaviors (g = .50), with an overall grand mean of g = .48. A meta-regression model showed that intervention program accounted for 83% of heterogeneity in the overall effect size for universal interventions. Overall, this meta-analysis demonstrated that preschool children benefit from SEL interventions in different contexts, particularly those who were identified as being in need of early intervention. Moreover, best practices for preschool SEL interventions may differ from best practices for K–12 students, given the developmental uniqueness of the preschool years.